2017
DOI: 10.1002/anie.201709970
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stability of Lanthanum Superhydrides

Abstract: Recent theoretical calculations predict that megabar pressure stabilizes very hydrogen-rich simple compounds having new clathrate-like structures and remarkable electronic properties including room-temperature superconductivity. X-ray diffraction and optical studies demonstrate that superhydrides of lanthanum can be synthesized with La atoms in an fcc lattice at 170 GPa upon heating to about 1000 K. The results match the predicted cubic metallic phase of LaH having cages of thirty-two hydrogen atoms surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
175
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 32 publications
20
175
2
Order By: Relevance
“…This is completely consistent with the fcc arrangement of La atoms found experimentally [3]. However, Geballe et al [20] observed a rhombohedral distortion below ∼160 GPa, with an R-3m space group for the La sublattice and a rhombohedral angle of approximately 61.3°(c/a ∼ 2.38 in the hexagonal representation). Our calculations show that this distortion is compatible with slight anisotropic stress conditions in the DAC.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…This is completely consistent with the fcc arrangement of La atoms found experimentally [3]. However, Geballe et al [20] observed a rhombohedral distortion below ∼160 GPa, with an R-3m space group for the La sublattice and a rhombohedral angle of approximately 61.3°(c/a ∼ 2.38 in the hexagonal representation). Our calculations show that this distortion is compatible with slight anisotropic stress conditions in the DAC.…”
supporting
confidence: 85%
“…A sodalite type-structure with space group F m-3m and T c ∼280 K was suggested above ∼220 GPa (see Fig. 1), and a distorted version of it below with space group C2/m and a rhombohedral La sublattice [19,20]. By laser heating a lanthanum sample in a hydrogen-rich atmosphere within a diamond anvil cell (DAC), a lanthanum superhydride was synthesized right after [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Much theoretical effort has devoted to the investigation of the superconductivity in the compressed hydrides, however, not many of the predicted phases were confirmed by the later experiments (for example, NaH 3 and NaH 7 [14], LiH 2 and LiH 6 [15], FeH 5 [16], NbH 2.5 and NbH 3 [17], Ni 2 H 3 [18], TaH 3 [19] and CoH 2 [18]). Recently, the astonishing discoveries of superconductivity with T c above 200 K in compressed H 2 S [20,21] and LaH 10 [6,[22][23], both initiated by previous theoretical works, suggested the feasibility of searching for high T c in hydrogen-rich materials at high pressures. These observations have generated a flurry of searching for new hydrogen-dominating superconductors under pressures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other hydrogen‐rich compounds have been predicted to be superconductors, e.g., LiH 6 , KH 6 , MgH 6 , CaH 6 , PbH 4 (H 2 ) 2 , AsH 8 , SbH 4 , YH 6 , ScH 6 , YH 10 , and LaH 10 . In a very recent study, Geballe et al successfully synthesized the lanthanum superhydride LaH 10 at 170 GPa and 1000 K in an experiment, which had the same clathrate‐like structure that was predicted previously . This reignited interest in searching for hydrogen‐rich compounds or the so‐called superhydrides (MH n with n > 5), considering that increasing the content of hydrogen promotes the probability of those materials behaving like the pure solid hydrogen .…”
Section: Introductionmentioning
confidence: 99%